Supervisi Pendidikan Islam (Studi atas Kontribusi Pengawas dalam Memotivasi dan Meningkatkan Profesionalisme Guru dalam Proses Pembelajaran di Sumenep) - Abd Warits (Institut Ilmu Keislaman Annuqayah, 2015)
The main function of educational supervision is to maintain the quality of management. A supervisor has to ascertain that learning and teaching process is basicly in line with national standards of education. Additionally, a supervisor has to do some important functions, including facilitating, choching, and guiding of teachers to advance their quality of teaching. The improvement of quality of education could be possible by increasing professionalism of teaching and learning, and hence the need for supervision of education as a partnership of teachers is necessary for advancing their competency and knowledge. This study attempts to figure out the role of educational supervision in Sumenep, Madura, in order to encourage teachers’ competencies and improve the better learning process. By using descriptive based qualitative approach, this study is aimed to address teacher’s performance and competence in educational system. The study provides a sympthomatic result that a lack of supervision has effects on the some degrees of decreased quality of education in Sumenep. It is a side-effect of some causes: burdened scope of tasks, lower level of teacher’s motivation, and any limited access of islamic institutions. However, some educational advisors in Sumenep get started with some efforts of improving the quality of teacher’s performance. They have encouraged them to actively get inovolve with forum of teacher workgroup and to attend some seminars, training, and workshop.